Land Acquisition Law in Indonesia: Between Legal Certainty and Substantive Injustice - Eka Sihombing, Irene; R. Arranchado, Jimi Rambo (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2026)
The issue of land acquisition for public-interest development in Indonesia is inseparable from the limited availability of state land and the predominance of privately and communally owned land. Although Indonesia has established a relatively comprehensive legal framework, its implementation still falls short of providing fairness and legal certainty. This situation raises an important question concerning the balance between state development agendas and the protection of community land rights. The main problem lies in a structural imbalance that may generate injustice rather than promote public welfare. This study examines the effectiveness of land acquisition law in ensuring legal certainty and realizing social welfare. Using a normative juridical method, this research draws on legal materials such as statutes, court decisions, legal doctrines, and academic literature. The findings show a gap between legal norms and their practical application. While the law sets out clear procedures, its substance and implementation often fail to ensure substantive justice, especially for indigenous communities and informal landholders. The novelty of this study lies in its utilitarian perspective, emphasizing that law should create the greatest benefit for the greatest number. This research recommends strengthening legal substance, improving compensation mechanisms, and harmonizing state law with customary law.